Gender Differences on Visual Imagery Among Table Tennis and Cricket Players: A study on gender differences in visual imagery among table tennis and cricket players (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Thepurpose of the present study was to analyse the visual imagery among men andwomen of table tennis, tennis and cricket players. To achieve the purpose ofthe study, a total of 90 subjects (men (n=45) and women (n=45)) were selectedrandomly as subjects. The present study consists of two categories ofindependent variables namely, gender (factor A) and different games (factor B).The first independent variable is related to men and women and the secondindependent variable consists of three games such as table tennis, tennis andcricket. The dependent variable selected for the study is mental imagery. Themental imagery was measured MIQ questionnaire which was developed byRajamanickam in the year 1995. The two-way factorial (2 X 3) analysis ofvariance (ANOVA) was used to evaluate the influence of the two categories ofvariables on the dependent variable. The result of the study shows that therewas no significant difference among the paired means of interaction factor A XB on visual imagery.